2022
DOI: 10.3389/fcvm.2022.979745
|View full text |Cite
|
Sign up to set email alerts
|

Sox13 is a novel flow-sensitive transcription factor that prevents inflammation by repressing chemokine expression in endothelial cells

Abstract: Atherosclerosis is a chronic inflammatory disease and occurs preferentially in arterial regions exposed to disturbed blood flow (d-flow) while the stable flow (s-flow) regions are spared. D-flow induces endothelial inflammation and atherosclerosis by regulating endothelial gene expression partly through the flow-sensitive transcription factors (FSTFs). Most FSTFs, including the well-known Kruppel-like factors KLF2 and KLF4, have been identified from in vitro studies using cultured endothelial cells (ECs). Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“… 58 , 59 While SOX TFs have been described to act during differentiation as well as to act vasoprotective in the mature endothelium, GATA TFs were shown to be upregulated by atheroprone FSS. For instance, Sox18 has been shown to regulate EC barrier integrity upon application of FSS in pulmonary arterial ECs, 60 FSS-dependent upregulation of SOX13 was connected to suppression of pro-inflammatory gene expression 31 and SOX17 acts as a critical regulator of vascular homoeostasis, commonly mutated in pulmonary arterial hypertension patients. 61 In contrast, elevated levels of GATA3 were connected to endothelial-mesenchymal transition-mediated pulmonary arterial hypertension (PAH), 62 GATA2 was shown to directly repress atheroprotective TF KLF2, 63 and GATA1/4 expression was elevated by pulsatile oscillatory atheroprone shear stress in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 , 59 While SOX TFs have been described to act during differentiation as well as to act vasoprotective in the mature endothelium, GATA TFs were shown to be upregulated by atheroprone FSS. For instance, Sox18 has been shown to regulate EC barrier integrity upon application of FSS in pulmonary arterial ECs, 60 FSS-dependent upregulation of SOX13 was connected to suppression of pro-inflammatory gene expression 31 and SOX17 acts as a critical regulator of vascular homoeostasis, commonly mutated in pulmonary arterial hypertension patients. 61 In contrast, elevated levels of GATA3 were connected to endothelial-mesenchymal transition-mediated pulmonary arterial hypertension (PAH), 62 GATA2 was shown to directly repress atheroprotective TF KLF2, 63 and GATA1/4 expression was elevated by pulsatile oscillatory atheroprone shear stress in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Recently, it was shown that SOX13, a member of the SOX pioneer TF family, 30 is robustly upregulated by FSS and suppresses pro-inflammatory gene expression. 31 Similarly, pioneer TF KLF4 mediates vasculo-protective gene expression in response to FSS. 32 On the other hand, GATA TFs have been shown to be upregulated by atheroprone FSS.…”
Section: Introductionmentioning
confidence: 99%
“…A study published in 2022 identified SOX13 as a novel flow-sensitive transcription factor. Disturbed flow represses the expression of SOX13 , which in turn leads to a strong induction of pro-inflammatory cytokine and chemokine production, including CCL5 and CXCL10, resulting in endothelial inflammation 134 .…”
Section: Mechanosensors and Mechanotransductionmentioning
confidence: 99%
“…[14,19,20] For instance, the application of oscillatory shear stress to endothelial cells will lead to NLRP3 (NLR family, pyrin domain containing 3) mediated inflammation by activating sterol regulatory element binding protein 2, [21] and flow-sensitive transcription factor SOX13 can prevent the inflammation by suppressing chemokine expression. [22] Nonetheless, the complexities of the vascular geometry in vivo coupled with the presence of confounding factors such as red blood cells, dynamic blood pressure, and immune responses, render the vascular model difficult to control in vitro. [23,24] Even the assessment of the effects requires substantial simplification of the in vivo context.…”
Section: Introductionmentioning
confidence: 99%